(untitled) (Environment & Health, 2025)
Aim. To summarize current scientific approaches to primary, secondary, and tertiary prevention of metabolic syndrome (MetS) in the context of war and emergencies. Materials and Methods. A narrative review was conducted to analyze changes in risk factors, access to medical care, and the effectiveness of MetS prevention during wartime. The analysis included sources from WHO, IDF, ADA, AACE, NICE, open-access databases, and the authors’ own data. Results. A comparison of all levels of MetS prevention during peacetime and emergencies showed that war leads to decreased access to healthcare, increased psychosocial stress, poorer nutrition, and reduced physical activity. These factors hinder both primary prevention and treatment at the secondary and tertiary levels. Consequently, the risk of MetS development increases, and the management of its components, hypertension, insulin resistance/diabetes, and dyslipidemia, becomes more challenging. However, the introduction of telemedicine, mobile medical teams, and simplified screening algorithms helps to partially address these issues. Based on the literature review, specific recommendations for MS prevention in crisis settings were developed. Conclusions. Metabolic syndrome is a complex clinical and biochemical condition associated with a high risk of complications. Its prevention during war and emergencies requires a multi-level, systemic approach that takes into account pathogenesis, comorbidities, psycho-emotional burden, and limited access to resources. The proposed system includes both general clinical principles proven effective in practice and a structured model of primary, secondary, and tertiary prevention. Its implementation enables the adaptation of care delivery to crisis settings, reduces the risk of complications, and helps preserve population health even in wartime conditions.